Software Requirements Elicitation for Complex Systems with the Functional Resonance Analysis Method (FRAM) - Carvalho, Elaine Alves; Gomes, José Orlando; Jatobá, Alessandro; Silva, Mônica Ferreira; Carvalho, Paulo Victor Rodrigues (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Despite all efforts, the requirements elicitation task is still considered non-trivial, especially for complex (non-linear) systems. In these systems, technological support must perform more resiliently, that is, be more adaptable to deal with uncertain situations. The Resilience Engineering provides the Functional Resonance Analysis Method (FRAM) to model these systems based on a description of the actual work (Work-As-Done - WAD). Therefore, unexpected events commonly associated with variability and improvisations become more explicit with that method. Thus, a multidisciplinary approach can contribute to requirements elicitation, since FRAM models deal with variability, unpredictability, and adaptation in complex socio-technical systems. This study applies Design Science Research to project a heuristic model to gather information from FRAM models to elicit functional and non-functional requirements, showing the contributions of Resilience Engineering to Requirements Engineering to identify software requirements for complex systems.